Jasa Pendidikan Jerman dan Indonesia - Rizka Meinarti (Musamus Journal of Public Administration, 2023)
Indonesia and Germany are two countries with different education systems that share the same goal of developing quality education. Cooperation between Germany and Indonesia is very important because of the potential to improve the quality of education in Indonesia. The purpose of this study is to present a comprehensive picture of education services, scholarships and cooperation between Germany and Indonesia. This research is a qualitative type which is described descriptively with a literature study approach. Literature study is used to collect and analyze various sources of information. This study uses narrative analysis techniques to analyze, understand and interpret narrative data. The results of the study reveal that Germany has a better education than Indonesia. The arrival of international students is strongly supported by Germany, as evidenced by the many scholarships awarded to various developing countries. Apart from scholarships, partner schools are also provided to prepare students and attract qualified foreign workers. This is Germany's effort to get a lot of foreign workers, considering the German population is not balanced with the number of available job vacancies. This effort aims to maintain the stability of the economic industry and also the welfare of the lives of all German people. This phenomenon illustrates that Germany gets more benefits from the practice of education services because Germany needs human resources to save their lives.